2020
DOI: 10.1038/s43018-020-0087-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pan-cancer image-based detection of clinically actionable genetic alterations

Abstract: This is a repository copy of Pan-cancer image-based detection of clinically actionable genetic alterations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
397
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 441 publications
(417 citation statements)
references
References 54 publications
18
397
2
Order By: Relevance
“…We included patients from the following 4 previous studies with the intent of retraining a previously described deep learning system. 16,17 First, we used the publicly available Cancer Genome Atlas (TCGA) (n ¼ 616 patients) ( Supplementary Figure 1), a multicenter study with patients with stage I-IV disease, mainly from the United States. 20 All images and data from the TCGA study are publicly available at https://portal.gdc.cancer.gov.…”
Section: Ethics Statement and Patient Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included patients from the following 4 previous studies with the intent of retraining a previously described deep learning system. 16,17 First, we used the publicly available Cancer Genome Atlas (TCGA) (n ¼ 616 patients) ( Supplementary Figure 1), a multicenter study with patients with stage I-IV disease, mainly from the United States. 20 All images and data from the TCGA study are publicly available at https://portal.gdc.cancer.gov.…”
Section: Ethics Statement and Patient Cohortsmentioning
confidence: 99%
“…30 A modified shufflenet deep learning system with a 512 Â 512 input layer was trained on these image tiles in MATLAB R2019a (Math-Works, Natick, MA) with the hyperparameters listed in Supplementary Table 3, as described before. 17 Tile-level predictions were averaged on the patient level, with the proportion of predicted MSI or dMMR tiles (positive threshold) being the free parameter for the receiver operating characteristic analysis. All confidence intervals were obtained by 10-fold bootstrapping.…”
Section: Image Preprocessing and Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published over the past 1-2 years have pursued a "pan-cancer pan-mutation" approach to try to predict any genetic alteration in any type of solid tumour directly from H&E histology. [38][39][40] However, these studies have been largely based on one particular dataset, "The Cancer Genome Atlas (TCGA)", provided by the National Cancer Institute (NCI), and so large-scale validation in genomically characterised cohorts beyond TCGA is needed to gauge the robustness of these methods in pancancer applications.…”
Section: Prediction Of Genotype and Gene Expressionmentioning
confidence: 99%
“…A recent pan-cancer study confirmed this finding by analyzing the histopathological images of more than 5,000 patients across 14 solid tumor types using deep learning. This study demonstrated the feasibility of identifying genetic variants, gene expression signatures, and clinical biomarkers from images 16 . There are also a small number of recent studies showing that collectively analyzing molecular and imaging data can improve prediction.…”
mentioning
confidence: 84%